2004
DOI: 10.1007/s11661-004-0072-1
|View full text |Cite
|
Sign up to set email alerts
|

Tensile and fatigue behavior of Al-based metal matrix composites reinforced with continuous carbon or alumina fibers: Part II. Quasi-unidirectional composite cross-ply laminates

R. Valle,
M.-H. Vidal-Sétif,
D. Schuster
et al.

Abstract: The mechanical behavior (tension, fatigue, and notch sensitivity) of Al-based metal matrix composite (MMC) cross-ply laminates is investigated. The two selected laminates, K139/A357 and N610/AU2, are reinforced by continuous K139 (carbon) or N610 (alumina) fibers. These multiplies consist in the stacking of (quasi-unidirectional) quasi-UD preforms oriented at 0, Ϯ45, and 90 deg, the thermomechanical behavior of the corresponding quasi-UD composites being reported independently (Part I). The investigated cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Two of commonly used reinforcing material types in metal matrix are ceramic and carbon-based material [25-29]. Metal matrix composites can be categorised into four subgroups depending on shape of reinforcing materials, such as particle reinforced metal matrix composite [30], continuous fibre reinforced metal matrix composite [31], short fibre or whisker reinforced metal matrix composite [32]and hybrid metal matrix composite with more than one type of reinforcements [33]. Mechanical properties of MMC depend on the type of matrix, type of reinforcement and their concentration, microstructure and fabrication process [34].…”
Section: Metal Matrix and Nano-reinforcementsmentioning
confidence: 99%
“…Two of commonly used reinforcing material types in metal matrix are ceramic and carbon-based material [25-29]. Metal matrix composites can be categorised into four subgroups depending on shape of reinforcing materials, such as particle reinforced metal matrix composite [30], continuous fibre reinforced metal matrix composite [31], short fibre or whisker reinforced metal matrix composite [32]and hybrid metal matrix composite with more than one type of reinforcements [33]. Mechanical properties of MMC depend on the type of matrix, type of reinforcement and their concentration, microstructure and fabrication process [34].…”
Section: Metal Matrix and Nano-reinforcementsmentioning
confidence: 99%
“…Friction coefficient and wear loss decreased as the carbon fiber volume fraction increased [16]. Tensile and shear properties, fatigue performance, and fracture toughness of such composites are also investigated, specifically for the effect of interfacial bonding conditions on the mechanical properties of the composite [17][18][19][20][21]. Studies have shown that the heat treatment of the composite to achieve precipitation hardening in the matrix can lead to sufficient residual thermal stresses to damage the fibers [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although the study of the mechanical properties and damage mechanisms of the quasi-UD composites represents a broader investigation involving acoustic emission monitoring, [10,11] only those of the results that are essential in the understanding of the specific behavior of this type of composite are reported in the present article (Part I). The next article (Part II [12] ) will be devoted to the quasi-UD (0, Ϯ45, 90 deg) laminates. Moreover, at a more theoretical viewpoint, due to the presence of the fibers and to the specific aspect of the quasi-UD preform, an exacerbation of the fatigue mechanisms occurring in the matrix, even more severe than in "model" UD composites, [13,14,15] may be expected.…”
Section: Introductionmentioning
confidence: 99%